2006
DOI: 10.1177/104063870601800204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism Pattern of the Fiber Gene and Pathogenicity of Serotype-1 Fowl Adenovirus Isolates from Gizzard Erosions and from Feces of Clinically Healthy Chickens in Japan

Abstract: Abstract. The fiber gene sequence and pathogenicity of the serotype-1 fowl adenovirus (FAdV-1) isolated from gizzard erosions and from clinically normal chickens were compared among isolates. The FAdV-99ZH strain, which induced gizzard erosions, had a nucleotide sequence of the long fiber gene that was different from that of the Ote strain, which did not induce gizzard erosions. The differences could be distinguished by use of polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 19 publications
5
45
0
Order By: Relevance
“…Meanwhile, the genome size of our Saudi isolate of FAdV-4 is about 3 kb shorter than that of the North American isolate. Furthermore, the isolate of this study seems to be very close to the newly reported FAdV-4 from China (22,24). The phylogram clearly shows that the reported isolates from eastern Saudi Arabia were clustered together with other Asian strains.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Meanwhile, the genome size of our Saudi isolate of FAdV-4 is about 3 kb shorter than that of the North American isolate. Furthermore, the isolate of this study seems to be very close to the newly reported FAdV-4 from China (22,24). The phylogram clearly shows that the reported isolates from eastern Saudi Arabia were clustered together with other Asian strains.…”
Section: Discussionmentioning
confidence: 59%
“…This variation among the FAdV-4 strains may contribute to the viral virulence. The Asian strains seem to be more virulent than the other strains of FAdV-4 reported from North America (3,17,22). Furthermore, the sequencing analysis of the partial hexon gene revealed the high similarity of the FAdV-4 strain isolated in this study to those from Kuwait, India, Pakistan, and China (data not shown).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Adenovirus infections may cause the clinical form of diseases such as inclusion body hepatitis (IBH) (Singh et al 2006), hydropericardium syndrome (HP) (Geanesh et al 2002), haemorrhagic enteritis virus (HE) (Hess et al 1999, Mazur-Lech et al 2009), Egg drop syndrome (EDS) (Dhinakar et al 2003) or gizzard erosion and ulceration (GEU) (Okuda et al 2006). Such infections play an important role in polietiological infections of the respiratory and digestive tract (Hess 2000, McConnell andFitzgerald 2008) or may proceed without any clinical signs of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In one case they can cause asymptomatic infections, in another they are an aetiological agent of diseases such as inclusion body hepatitis -IBH (6,19) or hydropericardium hepatitis syndrome -HHS (14). The viruses have been also isolated from birds with respiratory tract diseases (22), gizzard erosion and ulceration (GEU) (5,21,23), and pancreatitis (30). Adenoviruses can be the reason of immunodeficiency in young chicks, that can further lead to suppression of the immunity after the vaccination against Marek's disease.…”
mentioning
confidence: 99%